Effect of Unstable Macroeconomic Indicators on Banking Sector Stock Price Behaviour in Nigerian Stock Market - Abdullahi, Ibrahim Bello (International Journal of Economics and Financial Issues, 2020)
Stable macroeconomic environment is critical to an efficient stock market and economic growth. Banking sector plays important role in sustaining the growth in Nigerian stock market. However, the effect of unstable macroeconomic factors on the sector’s stock returns over the years cannot be ignored. This study seeks to investigate banking sector’s stock price behavior in response to unstable macroeconomic variables in Nigerian stock market. Autoregressive Distributed Lag (ARDL) model was employed to examine both short run and long run effects on the study variables between 2009 and 2018. Findings revealed negative significant effects of interest rate and foreign reserves on the stock price behavior of the banking sector both in the short run and long run with -0.21 and -9.004 respectively. Inflation rate has positive significant influence of 0.42, while exchange rate is not statistically significant in influencing stock price behavior in Nigerian stock market, all at 1% level of significance. The study concludes that, banking sector stock price is being influenced by foreign external reserve, interest rate and inflation rate. The study recommends that monetary policy rate should be reduced in order to lower the cost of borrowings and enhance liquidity level in the stock market. Keywords: ARDL Co-integration, Banking sector, Macroeconomic indicators, Nigerian stock market, Stock price behavior JEL Classifications: E02, G12 DOI: https://doi.org/10.32479/ijefi.9041